Celebrização da política e comunicação audiovisual em redes sociais digitais : o esforço de construção da imagem pública de João Doria Jr. por meio de vídeos no Facebook - Pablo Nogueira Santos Silva (2020)
This Master’s thesis aims to investigate the effort to build the political public image of João Doria Jr. during the first year of his term at the head of the city of São Paulo, by examining the videos posted by his team on the social networking site Facebook. In this work, we aim to point the strategies adopted by the Mayor to be noticed and identify, through his speech, what representations were performed, in order to be known and recognized by certain characteristics. For this, we made several studies able to assist in understanding our research object. First, we discoursed about “political celebrization” and “political celebrity”, concepts we found important to explain the trajectory and visibility forms of João Dória Jr. We considered yet the material found in digital social networks about comunication and political comunication and the role of the visualities communication and, last, we dealed with “public image” and “representation” in the closure of the theoretical part of this study. Then, we dedicated ourselves to the methodological chapter, in order to build, categorize our corpus and bound the observations made in the last chapter. Finally, we examined the videos, in order to answer our research questions.